THE EXPLORATION OF MATHEMATICS CONCEPT ON THE JAVANESE CALENDRICL SYSTEM BY JAVANESE COMMUNITY IN BENGKULU WITHIN ETHNOMATHEMATICS PERSPECTIVE - Ike Kurniawati; Herman Lusa (Universitas Majalengka, 2025)
The Javanese calendrical system is rich in history, philosophy, and math. This ethnomathematical study examined Javanese calendar mathematical concepts and their potential as a learning resource for elementary mathematics. This qualitative research collected data through direct observation, interviews, and literature review. The study used Miles and Huberman's analysis model for data reduction, display, and conclusion drawing. The Javanese calendrical system—Saka Year, Wetonan, lunar cycles, solar cycles, Pasaran, and Wuku cycles—is closely linked to elementary school math concepts. These include time calculations, pattern recognition, cyclical sequences, measurement, whole numbers, fractions, and conversions. The study found how incorporating the Javanese calendar into mathematics education to improve students' contextual understanding and make learning more engaging and culturally relevant. This study emphasizes ethnomathematics' role in meaningful learning by integrating mathematics with local culture. The Javanese calendar connects abstract mathematical theories to real-world applications through interactive education. The study suggests that ethnomathematics can boost student engagement, critical thinking, and cultural appreciation.